"Snow days are the best days." Exploring Teachers' and Administrators’ Perceptions of Weather-Related School Disruptions - Button, Brenton; Ouellette, Carson; Martin, Gina (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
Extreme weather events are becoming increasingly common and have the potential to impact the school day. This study aimed to explore teachers’ and administrators’ perspectives on weather-related school closures. Semi-structured interviews were conducted with ten key informants and analyzed using content analysis. Informants took a strengths-based approach and discussed the benefits of weather-related disruptions for student mental health and planning time. However, informants did mention that if these days continued to rise, it might be a cause for concern. School boards need to begin monitoring the impact of weather events.